Item-based foreign language learning of give ditransitive constructions: Evidence from corpus research. (December 2016) - Xu, Qi
Abstract: This paper incorporates corpus contrastive interlanguage analysis and usage-based approaches to language acquisition to study English ditransitive constructions of the verb give as used by Chinese EFL (English as a Foreign Language) learners at different proficiency levels. A contrastive analysis was carried out between a learner corpus – The Chinese Learner English Corpus and a native English corpus – The Louvain Corpus of Native English Essays . The findings show that beginning EFL learners tend to frequently use pronouns (as indirect object), short constituents, and certain concrete semantic classes. In addition, they also make erroneous use of give ditransitive constructions. At higher English proficiency levels, however, learners tend to use more complex structures containing noun phrases, longer constituents, and a wider range of semantic classes. The findings offer useful insights into the Chinese EFL learners' developmental trajectory of ditransitive constructions, and provide further evidence for the usage-based model, by showing an item-based foreign language learning process of give ditransitive constructions. The paper then concludes with a discussion of the pedagogical implications for classroom teaching practice and compiling teaching materials.